PUBLICATIONS OF THE WEEK. (Bookseller, 2003)
The article provides bibliographic information on several book titles to be published in 2003. Kusum Budhwar is the author of the book 'Romance of the Mango: The Complete Book of the King ofFruits.' 'F-117 Nighthawk,' by Paul F. Crickmore is a book on military aircrafts. There are several books on the theme of sculptures. 'Comprehensibility of the Universe: A New Conception of Science,' by Nicholas Maxwell is a book on astronomy.